Mechanistic insights into SIRT7 and EZH2 regulation of cisplatin resistance in bladder cancer cells - Yudong Cao; Shuo Wang; Jinchao Ma; Mengping Long; Xiuli Ma; Xiao Yang; Yongpeng Ji; Xingxing Tang; Jia Liu; Chen Lin; Yong Yang; Peng Du (Cell Death and Disease)
Abstract Cisplatin (CDDP) resistance has been established to significantly impact Bladder Cancer (BCa) therapy. On the other hand, the crucial regulatory involvement of SIRT7 and EZH2 in bladder cancer development is well known. Herein, the collaborative regulatory roles and underlying mechanisms of SIRT7 and EZH2 in CDDP resistance in bladder cancer were explored. Immunohistochemistry (IHC) and Western Blot (WB) analyses were used to assess the expression levels of SIRT7/EZH2 and RND3 in bladder cancer tissues, normal ureteral epithelial cells, and bladder cancer cell lines. Furthermore, the impact of various treatments on of UMUC3 cell proliferation and CDDP sensitivity was assessed using CCK-8 assays, plate cloning assays, and flow cytometry analysis. Additionally, the levels of H3K18ac and H3K27me3 at the promoter region of the RND3 gene, the binding abilities of SIRT7 and EZH2, and the succinylation level of the EZH2 protein were examined using ChIP-qPCR assays, CO-IP assays, and IP assays, respectively. Moreover, in vivo experiments were conducted using a bladder cancer mouse model created by subcutaneously injecting UMUC3 cells into Balb/c nude mice. According to the results, SIRT7 correlated with the sensitivity of bladder cancer cells to both the platinum-based chemotherapy and CDDP. Specifically, SIRT7 could bind to the RND3 promoter, downregulating H3K18ac and RND3, ultimately leading to an increased CDDP sensitivity in UMUC3 cells. Furthermore, EZH2 siRNA could decrease H3K27me3 levels in the RND3 promoter, upregulating RND3. Overall, in the promoter region of the RND3 gene, SIRT7 upregulated H3K27me3 and EZH2 downregulated H3K18ac, leading to a decline in RND3 expression and CDDP sensitivity in bladder cancer cells. Additionally, SIRT7 reduced the succinylation of the EZH2 protein resulting in an EZH2-mediated RND3 downregulation. Therefore, targeting SIRT7 and EZH2 could be a viable approach to enhancing CDDP efficacy in bladder cancer treatment.